The influence of genetic factors on the pathogenesis of hypertrophic scars and keloids - Liberski, Sławomir; Marczak, Daria; Migdalski, Arkadiusz (Journal of Education, Health and Sport, 2018)
Hypertrophic scars and keloids are forms of abnormal scarring, which may be the cause of somatic ailmants and, due to unfavorable aesthetic effect, also mental disorders and social problems. Given the unclear aetiology and the lack of effective treatment methods, they pose a serious challenge for modern science. The contribution of genetic factors is one of the proposed hypotheses regarding the formation of hypertrophic scars and keloids. Gene polymorphism and mutations occurring in them may interfere with the proper course of signaling pathways responsible for the subsequent stages of the wound healing process. An important role in the pathogenesis of abnormal scarring may be the TGF-B1/Smad pathway, MAPK kinase, pathway for IGF-I and its receptor, plasminogen activator inhibitor-1 and urokinase plasminogen activator, gene polymorphisms for the vitamin D receptor and the ADAM33 gene, as well as abnormal expression of suppressor genes. The effect on heat shock protein expression and type 2 hyaluronidase synthase was also shown. The explanation of the genetic basis of hypertrophic scar and keloid formation may lead to a full understanding of their pathogenesis and also have important implications in the form of therapeutic benefits resulting in the development of effective forms of treatment.